Building ceramsite for resource utilization of low-cost oil-based rock debris and preparation method of building ceramsite

By combining oil bedrock cuttings with waste oil-containing diatomaceous earth, building ceramics are prepared by simple process steps, which solves the problem of oil bedrock cutting treatment and the problem of high production cost of ceramics, and achieves high efficiency, environmental protection and low cost Resource utilization.

CN119430711APending Publication Date: 2025-02-14SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411400344.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively treat and resource utilization of oil bedrock cuttings, resulting in environmental pollution and waste of resources. At the same time, traditional ceramic production costs are high, the process is complex, and the utilization rate of oil bedrock cuttings is low.

Method used

Oil-bedded rock chips and waste oil-containing diatomaceous earth are used as raw materials to prepare building ceramics through steps such as drying, crushing, sieving, mixing, water addition, ultrasonic stirring and low-temperature sintering to achieve resource utilization of oil-bedded rock chips.

Benefits of technology

It realizes efficient resource utilization of oil bedrock chips, and prepares lightweight, high-strength, low water absorption and environmentally friendly building ceramics, which reduces production costs and energy consumption, and solves the problems of complex traditional ceramic processes and large resource consumption. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430711A_ABST
    Figure CN119430711A_ABST
Patent Text Reader

Abstract

The invention relates to the field of building materials, in particular to a preparation method of low-cost building ceramsite for resource utilization of oil-based rock debris, which is characterized by comprising the following steps: (1) respectively drying the oil-based rock debris and waste oil-containing diatomite to remove free water in the raw materials; (2) taking the dried oil-based rock debris and waste oil-containing diatomite in the step (1), crushing, sieving and mixing to obtain a mixture; (3) adding water into the mixture obtained in the step (2), mixing, and carrying out double-roller granulation to obtain raw material balls; and (4) calcining the raw material balls obtained in the step (3) at 1000-1100 DEG C for 10-20 minutes, and cooling to obtain the building ceramsite. The preparation method has the advantages of simple process, simple raw material components, large addition amount of oil-based rock debris, low energy consumption, no use of special additives and low cost, and the prepared building ceramsite has the advantages of high strength, low water absorption, environmental protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, in particular to a building ceramsite for resource utilization of low-cost oil-based rock cuttings and a preparation method thereof. Background Art

[0002] In recent years, the shortage of conventional natural gas resources and the optimization of energy structure have rapidly promoted the exploration and exploitation of shale gas. In the process of shale gas exploitation, in order to avoid the problems of hydration expansion and collapse and blockage of shale layers, oil-based drilling fluids are widely used to protect oil and gas layers, maintain hydrostatic pressure and well wall stability, and clean the bottom of the well. This has led to the large-scale production of oil-based cuttings. The petroleum pollutants, phenolic compounds, heavy metals and other toxic substances covered on their surfaces are biologically toxic, difficult to degrade and slow-release. They are difficult to handle and flammable, and have been listed as national hazardous wastes (National Hazardous Waste List, HW08). These pollutants are usually stored in waste mud cuttings pools in the well site. If they are discharged without treatment, stored for a long time or directly landfilled, they will cause serious harm to the ecological environment, animals and plants, and even human health, and will also cause a waste of resources.

[0003] With the increasing intensity of shale gas exploitation year by year, the harmless, resource-based and comprehensive utilization treatment technology of oil-based cuttings will become an inevitable trend in the development of oil-based cuttings treatment technology. At present, the harmless treatment of oil-based cuttings at home and abroad mainly includes solidification method, incineration method, pyrolysis method, biological treatment technology, extraction technology and room temperature deep desorption treatment technology, but it is subject to many problems such as cost, environmental protection and limited application of resource-based products. It is urgent to find a new material that is environmentally friendly, economical, simple in process, large in cuttings consumption and high in resource utilization rate to realize the resource treatment of oil-based cuttings.

[0004] Building ceramsite is a kind of man-made lightweight aggregate with strong adaptability. Due to its light weight, high strength, thermal insulation, fire resistance, earthquake resistance and excellent durability, it has great application prospects in the fields of building materials, roadbed materials, flower cultivation, water pollution treatment, etc. It is one of the fastest-growing new building materials in my country. At present, ceramsite sintered at high temperature with shale, clay, municipal sludge and other raw materials has excellent performance, but the cost is high, the production and application proportion of solid waste ceramsite is low, the material is not homogeneous, the resource consumption is large, and it is easy to cause landslides, water and soil imbalance and other problems. The solid phase composition of oil-based rock cuttings is similar to that of shale, sludge and other raw materials, and has the potential to prepare building ceramsite. If oil-based rock cuttings are used as raw materials for the preparation of building ceramsite, it can not only reduce costs, but also greatly promote the treatment and resource utilization of oil-based rock cuttings.

[0005] CN117466621A discloses a hollow ultra-light ceramsite based on oil-based rock debris and a preparation method thereof, which relates to the field of ceramsite, and comprises grinding and mixing oil-based rock debris residue, fluorine-containing sludge, high-carbon ferrochrome slag, and red mud to obtain a mixed raw material; adding water to the foaming agent microspheres and the mixed raw material to prepare green balls; roasting the green balls by a step-by-step roasting method, and obtaining hollow ultra-light ceramsite after cooling. In addition to the oil-based rock debris residue, this solution also adds other components such as fluorine-containing sludge, high-carbon ferrochrome slag, red mud, and foaming agent microspheres. In addition to the limited amount of oil-based rock debris residue, the process also involves a complex preparation process such as the preparation of foaming agent microspheres and step-by-step roasting, and the strength is not high.

[0006] Chen Xiaoyue's paper "Technology Research on Preparation of Ceramsite from Shale Gas Oil-Based Cuttings" (Issue 8, 2020) from Southwest University of Science and Technology records that based on the analysis of the characteristics of deep desorption treatment of oil-based cuttings, the oil-based cuttings and fly ash were used to prepare unfired ceramsite and sintered ceramsite, and borax pentahydrate was used as a flux to prepare low-energy low-temperature sintered ceramsite, which provides a certain theoretical and applied research basis for realizing the resource processing of oil-based cuttings and expanding the research and industrial application of oil-based cuttings in ceramsite. The research results show that when the ratio of fly ash to oil-based cuttings is 4:6 and the amount of water glass added per 500g of mixed powder is 75g, the obtained unfired ceramsite has a cylinder compressive strength of 5.1MPa, a water absorption rate of 8.57%, and an apparent density of 1993.0kg·m 3 The scheme requires the use of a specific flux to reduce energy consumption, and the cylinder compressive strength obtained after mixing with fly ash still needs to be further improved. Summary of the invention

[0007] The purpose of the present invention is to solve the above technical problems and provide a building ceramsite with the advantages of high strength, low water absorption, environmental protection and low cost for resource utilization of oil-based rock cuttings.

[0008] Another object of the present invention is to provide a method for preparing building ceramsite with simple process, simple raw material composition, large amount of oil-based rock cuttings added, low energy consumption, no use of special additives, and low cost and resource utilization of oil-based rock cuttings.

[0009] The method for preparing building ceramsite by low-cost resource utilization of oil-based rock cuttings of the present invention comprises the following steps:

[0010] (1) Drying the oil-based rock cuttings and the waste oil-containing diatomaceous earth separately to remove free water in the raw materials;

[0011] (2) taking the dried oil-based rock cuttings and waste oil-containing diatomaceous earth from step (1), crushing, sieving and mixing them to obtain a mixture;

[0012] (3) adding water to the mixture of step (2) and mixing, and granulating by double rollers to obtain raw material balls;

[0013] (4) calcining the raw material ball obtained in step (3) at 1000-1100°C for 10-20 min, and obtaining building ceramsite after cooling.

[0014] In the step (1), the drying temperature is 60-80°C, and the drying time is 6-10h.

[0015] In the step (2), the mixing ratio of the oil-based rock cuttings and the waste oil-containing diatomaceous earth is (7:3) to (9.5:0.5).

[0016] In the step (2), the oil content 1 in the mixture is controlled to be between 5% and 15% by mass.

[0017] In the step (2), the particle size of the oil-based rock cuttings and waste oil-containing diatomaceous earth after crushing and screening is controlled to be 80 mesh-160 mesh.

[0018] In the step (3), the solid-liquid ratio of the mixture to water is 6:1 to 4:1.

[0019] In the step (3), the mixture is mechanically stirred and mixed under ultrasonic conditions after water is added.

[0020] In the step (3), the ultrasonic conditions are as follows: the output power of each ultrasound is controlled at 400W-600W, the ultrasound time is 5min-10min, and there are 2 times in total, with an interval of 5min in between.

[0021] The building ceramsite for resource utilization of low-cost oil-based rock cuttings is prepared by the preparation method.

[0022] In view of the problems existing in the background technology, the inventor has made the following improvements:

[0023] (1) The ceramsite raw materials of the present invention contain only oil-based rock cuttings and waste oil-containing diatomaceous earth, and the raw materials are all hazardous wastes, which solves the prominent environmental problem that oil-based rock cuttings and waste oil-containing diatomaceous earth cannot be closed-loop, and realizes the resource utilization of large quantities of hazardous wastes. Here, the main benefits of selecting waste oil-containing waste diatomaceous earth as auxiliary materials are: first, using its stable SiO 2content, which can well supplement the oil-based rock cuttings and improve the stability of the raw materials; secondly, the waste oil-containing diatomaceous earth comes from the filtering and purification of rolling oil in the finishing of aluminum foil, which is a hazardous waste and contains a small amount of aluminum chips and other debris. After pretreatment processes such as grinding, these metal micropowders will participate in the reaction during the sintering process, promote the sintering of the ceramic shell, and form a certain amount of mullite crystal phase and other reinforcing phases to optimize the shell structure and performance; the oil content and porous properties of the waste oil-containing diatomaceous earth are cleverly used to solve the problems of uneven dispersion of voids inside the expanded clay, poor stability and low strength, thereby improving the strength and stability of the expanded clay; the product stacking density is regulated from a process perspective based on the oil content of the raw material system. Third, diatomite is mainly composed of the remains of ancient diatoms. It is a biogenic siliceous sedimentary rock with many orderly arranged mesopores (2-50nm) and macropores (>50nm) inside. This unique structure gives it the advantages of high porosity and high specific surface area, and also provides the original microporous structure inside the ceramsite. At the same time, waste oil-containing diatomite can add a certain amount of oil to the material system, and use oil substances to decompose and produce gas to form pores during the sintering process. Under the combined action of the original pore structure of diatomite, the pore structure caused by gas production and the formed liquid phase, it is easy to make the size and distribution of the pores inside the ceramsite after sintering more uniform, so that the ceramsite can meet the light weight requirements while ensuring its strength. Therefore, waste oil-containing diatomite is a very good match as an auxiliary. Here, the mixing ratio of the oil-based rock cuttings and the waste oil-containing diatomite is (7:3) to (9.5:0.5). In the absence of other auxiliaries or additives, the proportion of oil-based rock cuttings can reach up to 9.5, and the addition amount is high.

[0024] (2) Traditional mechanical stirring can make the material particles evenly distributed in the macroscopic view, but there are still uneven dispersion phenomena such as local agglomeration and partial aggregation, so it is necessary to age for 5-7 days to make the material as homogenized as possible. The present invention adopts mechanical stirring and mixing under ultrasonic conditions to achieve effective homogenization of the material, so no aging is required, which greatly shortens the process flow, can effectively improve the agglomeration phenomenon caused by oil content, and make the oil and material evenly distributed. The ultrasonic conditions are controlled to control the output power of each ultrasound to 400W-600W, the ultrasonic time is 5min-10min, a total of 2 times, and the interval is 5min. Under such conditions, on the one hand, the mechanical properties of the sintered ceramsite are improved, and on the other hand, the new crystal phase formed inside the ceramsite is more evenly distributed, the solidification effect of heavy metals is improved, the safety of the product in the resource utilization process is guaranteed, and there are certain environmental benefits.

[0025] (3) Compared with the sintering temperature of traditional ceramsite, which is generally above 1130℃, the process route of the present invention is mature, the sintering temperature range is low (1000-℃1100)℃, the energy-saving effect is good, and the production cost is low. On the one hand, the oil-containing characteristics of the two hazardous wastes can provide a certain amount of calorific value for the sintering process, thereby reducing the use of external heat sources and achieving energy-saving effects; on the other hand, SiO is formed during the sintering process. 2 -Al 2 O 3 -BaO-CaO system can make the material system form a new crystal phase at a lower melting point, while ensuring that all indicators of ceramsite meet relevant requirements. When producing the same density level, energy consumption is reduced by 30%-50%.

[0026] (4) The oil-based rock debris resource utilization construction expanded clay prepared by this method has the advantages of light weight, high strength, low water absorption, and environmental protection. Compared with the relevant indicators of the same density grade in the current standard "GB-T 17431.1-2010 Light Aggregate and Its Test Methods", the 1h water absorption rate is 6.4%-31.4% of the standard value, and the cylinder pressure strength is ordinary. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 (a) is a scanning electron microscope image of the raw material ball of Example 1 before sintering.

[0028] Figure 1 (b) is a scanning electron microscope image of the sintered ceramsite of Example 1.

[0029] FIG. 2( a ) is a scanning electron microscope image of the ceramsite after sintering the mixed materials in Comparative Example 1 using only mechanical stirring.

[0030] FIG. 2(B) is a scanning electron microscope image of the ceramsite of Example 2.

[0031] Specific embodiment

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Among them, the waste oil-containing diatomaceous earth comes from the finishing filtration and purification of rolling oil of aluminum foil, which is a hazardous waste. The waste oil-containing diatomaceous earth in the embodiments of the present invention comes from a certain aluminum industry company in Guangrao, Shandong, which produces aluminum plates, aluminum coils, and aluminum foils.

[0033] Embodiment 1:

[0034] The steps include:

[0035] (1) The selected oil-based rock cuttings and waste oil-containing diatomaceous earth are dried at 80° C. for 6 h to obtain a dry raw material.

[0036] (2) The oil-based rock cuttings and waste oil-containing diatomaceous earth dried in step (1) were crushed, passed through an 80-mesh sieve, and the two raw materials were mixed in a ratio of 7:3 to obtain a mixed sample with an oil content of 5%.

[0037] (3) Add water to the mixed sample of step (2) at a solid-liquid ratio of 6:1, and granulate the mixed materials by mechanical stirring + ultrasonic mixing to obtain raw material balls, wherein the ultrasonic power is 600 W and the ultrasonic time is 10 min.

[0038] (4) calcining the raw material obtained in step (3) at 1000° C. for 20 min, and obtaining the lightweight, high-strength, low-water-absorption, environmentally friendly oil-based rock chip resource utilization building ceramsite after cooling.

[0039] See also Figure 1 (a) and Figure 1 (b) Dry and grind the sample to be tested into powder, and then observe the microstructure of the sample using a scanning electron microscope. The test results are as follows: Figure 1 shown. Figure 1 (a) is the microscopic morphology of the ceramsite embryo. It can be seen from the observation that the structure inside the embryo is relatively loose and the block-like structure is dispersed. Figure 1 (b) is the microscopic morphology of the sintered ceramsite body after sintering, which is a typical ceramsite micromorphology. The ceramsite is mainly composed of three parts: crystal phase, glass phase and pores. The glass phase can wrap around the surface of the crystal phase, and can also wrap the gas to form pores. Figure 1 The larger pores in (b) are distributed relatively evenly, which are formed by the molten liquid phase encapsulating the gas during the sintering process. Therefore, the surface of the small pores is smooth, which improves the stability of the ceramsite structure and plays an extremely important role in the solidification of heavy metals in the ceramsite.

[0040] Embodiment 2:

[0041] This embodiment provides a method for preparing building ceramsite for resource utilization of oil-based rock cuttings, comprising the following steps:

[0042] (1) The selected oil-based rock cuttings and waste oil-containing diatomaceous earth are dried at 60° C. for 10 h to obtain a dry raw material.

[0043] (2) The oil-based rock cuttings and waste oil-containing diatomaceous earth dried in step (1) were crushed, passed through a 160-mesh sieve, and the two raw materials were mixed in a ratio of 9.5:0.5 to obtain a mixed sample with an oil content of 15%.

[0044] (3) Add water to the mixed sample of step (2) at a solid-liquid ratio of 4:1, and granulate the mixed materials by mechanical stirring + ultrasonic method to obtain raw material balls, wherein the ultrasonic power is 400 W and the ultrasonic time is 5 min.

[0045] (4) calcining the raw material obtained in step (3) at 1100° C. for 10 min, and obtaining the lightweight, high-strength, low-water-absorption, environmentally friendly oil-based rock chip resource utilization building ceramsite after cooling.

[0046] Embodiment 3:

[0047] This embodiment provides a method for preparing building ceramsite for resource utilization of oil-based rock cuttings, comprising the following steps:

[0048] (1) The selected oil-based rock cuttings and waste oil-containing diatomaceous earth are dried at 70° C. for 8 h to obtain a dry raw material.

[0049] (2) The oil-based rock cuttings and waste oil-containing diatomaceous earth dried in step (1) are crushed, passed through a 100-mesh sieve, and the two raw materials are mixed in a ratio of 8:2 to obtain a mixed sample with an oil content of 10%.

[0050] (3) Add water to the mixed sample of step (2) at a solid-liquid ratio of 4:1, and granulate the mixed materials by mechanical stirring + ultrasonic method to obtain raw material balls, wherein the ultrasonic power is 500 W and the ultrasonic time is 7 min.

[0051] (4) calcining the raw material obtained in step (3) at 1050° C. for 15 min, and obtaining the lightweight, high-strength, low-water-absorption, environmentally friendly oil-based rock chip resource utilization building ceramsite after cooling.

[0052] In order to demonstrate the performance, the main indexes of the oil-based rock cuttings resource utilization building ceramsite of Example 1, Example 2 and Example 3 of the present invention were tested, and the results are shown in Table 1.

[0053] Table 1 Performance test results

[0054]

[0055] The present invention obtains the production of 800-grade oil-based rock cuttings resource utilization building ceramsite, and the 1h water absorption rates of Example 1, Example 2 and Example 3 are 0.96%, 2.01% and 0.84% ​​respectively, and the cylinder pressure strengths are 24.64MPa, 15.54MPa and 24.92MPa respectively. The 1h water absorption rate and cylinder pressure strength of 800-grade aggregate in the standard of "GB_T17431.1-2010 Lightweight Aggregate and Test Methods" are 10% and 4MPa (6MPa for high-strength aggregate). Water absorption rate and cylinder pressure strength are important indicators of aggregate, which will affect various indicators such as workability, compressive strength and durability of concrete. It can be seen from the experimental results that the present invention is far higher than the values ​​specified by the current standards.

[0056] Comparative Example 1:

[0057] Compared with Example 3, the difference is that the calcination temperature used in step (4) is 980°C and the rest is the same as Example 3.

[0058] Comparative Example 2:

[0059] Compared with Example 3, the difference is that the calcination temperature used in step (4) is 1120°C and the rest is the same as Example 3.

[0060] In order to demonstrate the performance, the oil-based rock cuttings resource utilization building ceramsite obtained in Example 3 of the present invention, Comparative Example 1 and Comparative Example 2 were tested, and the results are shown in Table 2.

[0061] Table 2 Test results of relevant indicators

[0062]

[0063] The present invention obtains the production of 800-grade oil-based rock cuttings resource utilization building ceramsite, wherein the 1h water absorption rate and cylinder pressure strength of Example 3 are 0.96% and 24.92MPa respectively, the 1h water absorption rate and cylinder pressure strength of Comparative Example 1 are 9.17% and 4.12MPa respectively, and the 1h water absorption rate and cylinder pressure strength of Comparative Example 2 are 11.57% and 3.48MPa respectively. Although the performance indexes of Comparative Example 1 meet the standard values ​​of "GB_T 17431.1-2010 Light Aggregate and Its Test Method", the effect is worse than that of Example 3, and the product performance index obtained by Comparative Example 2 does not meet the standard values ​​of "GB_T 17431.1-2010 Light Aggregate and Its Test Method", the reason is that too low or too high temperature affects the reaction of the internal substances of the ceramsite and the formation of the crystal phase, thereby causing the performance of the product to decline. In terms of heavy metal leaching, the leaching concentration of Comparative Example 2 is higher than that of Example 3, indicating that Comparative Example 2 did not reach the reaction temperature and the solidification effect of heavy metals was poor; the leaching concentration of Comparative Example 1 was slightly lower than that of Example 3. The reason was that the excessively high temperature caused the structure of the heavy metals wrapped inside the ceramsite or the formed mineral phase to be decomposed at a higher temperature, and the heavy metals separated from the ceramsite and entered the flue gas. Combined with the performance indicators, it is believed that Example 3 is better than Comparative Example 2.

[0064] Comparative Example 3:

[0065] Compared with Example 3, the difference is that in step (3), only mechanical stirring is used for mixing, and the rest is the same as Example 3.

[0066] In order to demonstrate the heavy metal solidification effect, the oil-based rock cuttings resource utilization building ceramsite obtained in Example 3 of the present invention and Comparative Example 3 was tested, and the results are shown in Table 3.

[0067] Table 3. Test results of relevant indicators

[0068]

[0069] The performance index and heavy metal leaching index of Example 3 are better than those of Comparative Example 3, indicating that the process can improve the performance index of ceramsite and the solidification effect on heavy metals.

[0070] Referring to Figure 2(a) and Figure 2(b), Figure 2(a) shows that the comparative example 2 adopts a single mechanical stirring method to mix the materials, and Figure 2(b) shows that the mechanical stirring + ultrasonic method is used to mix the materials in Example 3. It can be seen that compared with Figure 2(a), the internal void size and distribution of the expanded clay in Figure 2(b) are more uniform, and the agglomeration phenomenon is improved.

[0071] Comparative Example 4

[0072] Compared with Example 3, the difference is that ordinary diatomaceous earth is used to replace the waste oil-containing diatomaceous earth, and the rest is the same as Example 3.

[0073] In order to demonstrate the performance, the oil-based rock cuttings resource utilization building ceramsite obtained in Example 3 of the present invention and Comparative Example 3 was tested, and the results are shown in Table 4.

[0074] Table 3. Test results of relevant indicators

[0075]

[0076] The performance index of Example 3 is better than that of Comparative Example 4, indicating that the use of waste oil-containing diatomite can improve the performance index of ceramsite. Waste oil-containing diatomite contains a small amount of aluminum chips and other debris. After pretreatment processes such as grinding, these metal powders will participate in the reaction during the sintering process, promote the sintering of the ceramic shell, and form a certain amount of reinforcing phases such as mullite crystal phase to optimize the shell structure and performance.

Claims

1. A method for preparing building ceramsite by low-cost resource utilization of oil-based rock cuttings, characterized in that: The steps include: (1) Drying the oil-based rock cuttings and the waste oil-containing diatomaceous earth separately to remove free water in the raw materials; (2) taking the dried oil-based rock cuttings and waste oil-containing diatomaceous earth from step (1), crushing, sieving and mixing them to obtain a mixture; (3) adding water to the mixture of step (2) and mixing, and granulating by double rollers to obtain raw material balls; (4) calcining the raw material ball obtained in step (3) at 1000° C.-1100° C. for 10-20 min, and obtaining building ceramsite after cooling.

2. The method for preparing building ceramsite with low-cost oil-based rock cuttings resource utilization as claimed in claim 1, characterized in that: In the step (1), the drying temperature is 60° C.-80° C., and the drying time is 6-10 hours.

3. The method for preparing building ceramsite for low-cost oil-based rock cuttings resource utilization as claimed in claim 1, characterized in that: In the step (2), the mixing ratio of the oil-based rock cuttings and the waste oil-containing diatomaceous earth is (7:3) to (9.5:0.5).

4. The method for preparing building ceramsite with low-cost oil-based rock cuttings resource utilization as claimed in claim 3, characterized in that: In the step (2), the oil content 1 in the mixture is controlled to be between 5% and 15% by mass.

5. The method for preparing building ceramsite with low-cost oil-based rock cuttings resource utilization as claimed in claim 1, characterized in that: In the step (2), the particle size of the oil-based rock cuttings and waste oil-containing diatomaceous earth after crushing and screening is controlled to be 80 mesh-160 mesh.

6. The method for preparing building ceramsite for low-cost oil-based rock cuttings resource utilization as claimed in claim 1, characterized in that: In the step (3), the solid-liquid ratio of the mixture to water is (6:1) to (4:1).

7. The method for preparing building ceramsite for resource utilization of low-cost oil-based rock cuttings according to any one of claims 1 to 6, characterized in that: In the step (3), the mixture is mechanically stirred and mixed under ultrasonic conditions after water is added.

8. The method for preparing building ceramsite with low-cost oil-based rock cuttings resource utilization as claimed in claim 7, characterized in that: In the step (3), the ultrasonic conditions are as follows: the output power of each ultrasound is controlled at 400W-600W, the ultrasound time is 5min-10min, and there are 2 times in total, with an interval of 5min in between.

9. A low-cost oil-based rock cuttings resource utilization building ceramsite, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Hollow ultra-light ceramsite based on oil-based rock debris and preparation method of hollow ultra-light ceramsite

    CN117466621A